2021
DOI: 10.1080/14767058.2021.1907333
|View full text |Cite
|
Sign up to set email alerts
|

The application of expanded noninvasive prenatal screening for genome-wide chromosomal abnormalities and genetic counseling

Abstract: Objective: To evaluate the clinical application of expanded noninvasive prenatal screening (eNIPS) for genome-wide large copy number variation (CNV), i.e. chromosomal deletion/duplication >5 Mb, and aneuploidy; also to provide practical information for counseling eNIPS positive cases. Method: We recruited 34,620 women with singleton pregnancy for genome-wide cell-free plasma DNA sequencing. Screening positive cases were verified by karyotyping and/or SNP array. Result: A total of 461 (1.33%) positive cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…Many investigations indicated that NIPT‐plus was available to detect fetal chromosome CNVs (Chen et al, 2021; Kaseniit et al, 2018; Liang et al, 2019b; Wapner et al, 2015). The research of Helgeson et al confirmed that NIPT‐plus can reach a higher PPV of 60% ~ 100% via optimized bioinformatics algorithms for detecting CNVs (Helgeson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations indicated that NIPT‐plus was available to detect fetal chromosome CNVs (Chen et al, 2021; Kaseniit et al, 2018; Liang et al, 2019b; Wapner et al, 2015). The research of Helgeson et al confirmed that NIPT‐plus can reach a higher PPV of 60% ~ 100% via optimized bioinformatics algorithms for detecting CNVs (Helgeson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies solely evaluated the genome-wide detection of CNVs. Most of them screened for previously undiagnosed fetal CNVs [ 4 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], but two studies obtained samples with known CNVs and retrospectively conducted NIPT analysis [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies obtained plasma samples from the population of pregnant women who underwent NIPT without specifically defining referral indications for the screening [ 4 , 10 , 15 , 17 , 19 , 20 , 21 , 28 , 30 , 31 , 33 , 34 , 35 , 37 , 38 ]. Some included only samples of women with high-risk pregnancies (over 35 years of age), positive serum screening results, a history of aneuploidy, abnormal ultrasound findings, or simply maternal anxiety [ 22 , 32 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…NIPT also is utilized to screen for select microdeletions/microduplications and other rare autosomal trisomies but shows relatively poor positive predictive value (PPV) for these applications (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…CMA has become a first-tier diagnostic test at greater frequency across the globe, particularly when fetal anomalies are encountered. However, KT, FISH, MLPA and qPCR remain the tests of choice in many countries, primarily owing to financial and resource constraints (6,7,9,12).…”
Section: Introductionmentioning
confidence: 99%